CHARACTERIZING STAFF INTERACTIONS IN A SAMPLE OF HIGH PERFORMING NURSING HOMES. (11th November 2018) - Snow, A; Clark, V; Zhao, S; Nash, P; Allen, R; Bolton, R; Hartmann, C
Abstract: Increasing evidence indicates nursing home staff interactions with residents and each other contribute to care quality. We characterized interaction in a sample of top performing person-centered care (PCC) adopters in the Veterans Administration (VA) system of 134 Community Living Centers (CLCs– i.e., nursing homes). We identified 8 top-performing CLCs using a combination of quality and PCC indices. At these 8, staff participated in a validated survey of relational coordination. Researchers also conducted structured observations of staff and resident behavior in public areas. Analyses were descriptive. 392 staff responded to the survey. Researchers conducted 2, 459 observations. Across all CLCs, staff reported the quality of their interactions within (WI) their workgroup consistently lower than the quality of their interactions between (BW) their and other workgroups. BW ratings: 24% strong, 34% moderate, 42% weak. WI ratings: 92% weak. Strong ratings varied by workgroup type and by WI and BW. Nursing was more likely to receive strong ratings than other workgroups but less likely to assign strong ratings to other groups. 31% of observations were of staff performing direct resident care while communicating with the resident and 39% were of staff having no communication with the resident during care. Results in this top-performing sample indicate potential room for continued improvement. Given our findings of rather low relational coordination and interaction quality, quality improvement interventions directly targeting staff communication and staff-resident interaction might represent opportunities for positive impact not only in high PCC performers but across the PCC performance spectrum.